La importancia de la automatización de la auditoría de sistemas a través de procesos robóticos (RPA) (2022)
Automation (RPA), to expose the state of the art, to interpret the usefulness, and to conclude on the importance of applying RPA during the execution of the systems audit process. The absence or ignorance of handling emerging technologies such as RPA in systems auditing places the auditor at a competitive disadvantage against market demands, this impact has a negative impact on factors such as efficiency, productivity, quality of results and costs in the required tasks.